2011
DOI: 10.1002/jcc.21959
|View full text |Cite
|
Sign up to set email alerts
|

A computational chemist approach to gas sensors: Modeling the response of SnO2 to CO, O2, and H2O Gases

Abstract: A general bottom-up modeling strategy for gas sensor response to CO, O(2), H(2)O, and related mixtures exposure is demonstrated. In a first stage, we present first principles calculations that aimed at giving an unprecedented review of basic chemical mechanisms taking place at the sensor surface. Then, simulations of an operating gas sensor are performed via a mesoscopic model derived from calculated density functional theory data into a set of differential equations. Significant presence of catalytic oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 65 publications
3
31
0
Order By: Relevance
“…As observed already in synthetic air, no carbonyl-like donor species are formed. All in all, our results confirm the theoretical results reported recently 8,9 : the sensing of representative reducing gases, including humidity, seems to be governed by the interplay between surface reduction and reoxidation, which depends on the composition of the surrounding atmosphere, and will result in a certain concentration of oxygen vacancies i.e. surface charge and in the end sensor resistance.…”
Section: Acs Paragon Plus Environmentsupporting
confidence: 94%
See 3 more Smart Citations
“…As observed already in synthetic air, no carbonyl-like donor species are formed. All in all, our results confirm the theoretical results reported recently 8,9 : the sensing of representative reducing gases, including humidity, seems to be governed by the interplay between surface reduction and reoxidation, which depends on the composition of the surrounding atmosphere, and will result in a certain concentration of oxygen vacancies i.e. surface charge and in the end sensor resistance.…”
Section: Acs Paragon Plus Environmentsupporting
confidence: 94%
“…Besides the obvious consequences for the transduction -this switch has major implications on the effect of band bending changes onto the measured sensing layer resistance -there are significant implications also for the 3 reception: additional to the reaction with ionosorbed oxygen species we have to take into consideration also the direct reaction between the reducing gases and the SnO 2 surface. In the absence of experimental evidence, a good starting point is the theory: recent DFT calculations for SnO 2 (101) and (110) surfaces, published by J.-M. Ducéré et al 8 and X. Wang et al 9 respectively, give a detailed description of the charge-transfer associated with CO oxidation. Consistently, it was found that CO reacts with 2-fold coordinated (bridging) oxygen forming CO 2 and an oxygen vacancy (equation 1), which acts as an adsorption site for molecular and atomic oxygen species (equation 2).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the CO sensing mechanism of SnO 2 (110) surface [43][44][45][46][47], the sensing properties strongly depends upon the concentration of oxygen in the ambient atmosphere: CO reacts with either directly stoichiometric surface or oxygen species O − 2 or O − , accompanying the release of electrons to the surface with or without formation of CO 2 [43].…”
Section: Introductionmentioning
confidence: 99%